Experimental Study on the Morphology of Keratin Based Material for Asbestos Free Brake Pad - O.S. Olokode; S.O. Fakolujo; P.O. Aiyedun; Z.O. Jaji; F.T. Owoeye; B.U. Anyanwu (Journal of Basic & Applied Sciences, 2021)
This research was carried out to investigate the friction and wear of automotive materials using a pad on disk type friction tester to study the synergistic effects of bagasse (residue from sugarcane) and cow hooves dust (keratin based material). The friction materials were based on a simple formulation with three ingredients (phenolic resin, cow hooves dust and bagasse). Friction stability, hardness, compressive strength, flame resistance and oil absorption were measured. Microscopic observation of the friction material showed that the cow hooves adhered to the bagasse providing heat resistance and strength to the friction film at the rubbing interface. The beneficial synergistic effect from the two fibrous ingredients however was significantly diminished when only one of them was employed.